Analysis of The Effect of Entrepreneurial Literacy And Personal Characteristics On Innovative Capability Through Entrepreneurial Inspiration As A Mediating Variable - Sukarsih; Nasikh; Imam Mukhlis (Citakonsultindo, 2025)
This study aims to analyze the effect of entrepreneurial literacy and personal characteristics on innovative ability with entrepreneurial inspiration as a mediating variable in 11th grade students at State Vocational High Schools (SMKN) in Mojokerto Regency. A quantitative approach was used with a survey method through the distribution of questionnaires to 350 respondents selected proportionally. Data analysis was performed using the Partial Least Square Structural Equation Modeling (PLS-SEM) technique. The results showed that entrepreneurial literacy had a significant positive effect on innovative ability and entrepreneurial inspiration. Personal characteristics were also found to influence innovative ability and had a stronger effect on entrepreneurial inspiration than entrepreneurial literacy. Furthermore, entrepreneurial inspiration has a significant positive effect on innovative ability and is proven to mediate the influence of entrepreneurial literacy and personal characteristics on innovative ability. The mediation that occurs is partial, which means that entrepreneurial literacy and personal characteristics still have a direct effect on innovative ability, but this effect is strengthened through entrepreneurial inspiration. These findings indicate that developing the innovative abilities of vocational high school students requires not only improving their entrepreneurial knowledge, but also shaping their personal character and creating inspiring learning experiences. The practical implications of this study are the need for schools to strengthen practice-based curricula and build a supportive entrepreneurial ecosystem; teachers playing an active role as facilitators capable of fostering inspiration; and policy makers supporting entrepreneurial education programs that are integrated with the business and industrial world. Thus, this study contributes to strengthening theoretical and practical understanding of the relationship between entrepreneurial literacy, personal characteristics, entrepreneurial inspiration, and innovative abilities in vocational school students.